"THERE IS QUEER INEQUITY, BUT I PICK TO BE HAPPY": Racialized Feeling Rules and Diversity Regimes in University LGBTQ Resource Centers. (12th April 2021) - Ortiz, Stephanie M.; Mandala, Chad R.
Abstract: As racialized and gendered structures, organizations can reinforce complex inequalities, especially with regard to emotional labor. While the literature on emotional labor is established, little is known about how race and sexual orientation shape feeling rule enforcement. Interviewing staff at university LGBTQ resource centers, we argue that feeling rules have a sexual orientation-based dimension and are experienced and enforced differently based on race. White LGBTQ staff find that they can express anger strategically to bring awareness to issues of race, but do not confront racism in their work for fear of alienating other Whites, which they believe would harm their center. LGBTQ staff of color experience organizational consequences for their anger, which is directed toward the racism they and students of color experience in the university. Lacking the credential of Whiteness (Ray 2019), staff of color find they cannot reach the benchmark set by Whites' enthusiastic performance of emotional labor. These feeling rules operate in service of what James M. Thomas (2018) calls diversity regimes, which are performances of a benign commitment to racial equality, that retrench racial inequality by failing to redistribute resources along racial lines. By sanctioning anger toward the university—as an institution that reproduces racism—feeling rules have organizational consequences: Whites can advance through compliance and enthusiasm; staff of color are terminated or denied opportunities; and critiques of racism are silenced. While created to address diversity, LGBTQ centers are purposely not structurally positioned to radically shift resources in a way to combat racism, and feeling rules maintain these arrangements while allowing universities to claim a commitment to equality. These findings hold implications for broader concerns of racism, sexual orientation, and inequality within work organizations, especially manifestations of worker control within diversity work.